Portfolio construction and performance measurement for consumer products sector in the Kuala Lumpur Stock Exchange (KLSE) / Noor Majeedah Abdillah - Abdillah, Noor Majeedah (Faculty of Business Management, 2017)
This project paper focuses on the construction portfolio and measurement performance for the Consumer Products sector that is listed in Kuala Lumpur Stock Exchange (KLSE). The main issue or problem in this topic is about the methods that suitable for an investor to optimize the return of and reduce the risk in the portfolio. By using the construction portfolio and performance measurement on the stocks that an investor wants, they would know the stock that has the maximum portfolio return while minimizing the risk. The main objective of this study is to construct the optimum portfolio selection strategies and to measures the performance of Consumer Products sector in the context of Kuala Lumpur Composite Index (KLCI). In order to construct the portfolio of the stocks in the Consumer Products sector, the Simple Sharpe Portfolio Optimization or Efficient Frontier Model has been used from year 2006 until year 2010. In addition, the measures performance of Consumer Products sector is based on the Portfolio Management Performance Model (Sharpe Index, Treynor Index and Jensen Index) from the year 2011 until year 2015. The performance of the Consumer Products sector is compared with the market which is KLCI. The data collected from DataStream provided by UiTM. The data needed is Return Index for every stock, beta for every stock, Return Index for KLCI, and the 3 month Treasury bill Discount Rate for the risk-free rate. The Abnormal Return measurement is used in order to know the expectancy between the return portfolios and return market. The pair T-Test is used for the compare the performance of the selection stocks with the market which is KLCI. After the analysis of data from 130 companies from Consumer Products sector listed in KLSE, there is only 92 companies from Consumer Products sector that have an appropriate data to be included in this research study. For the Simple Sharpe Portfolio Optimization or Efficient Frontier Model, the 92 stocks from Consumer Products sector is construct in the portfolio selection strategies to get the optimum portfolio selection strategies. After that, the best companies will be selected and evaluate in the Portfolio Management Performance Model (Sharpe Index, Treynor Index and Jensen Index). In the performance measurement of the Consumer Products sector, there are also 17 stocks from Consumer Products sector to be included in this research study. The companies from the Consumer Products sector will be rank based on its performance and then compare with the market performance which is the KLCI.